South Indian Children's Neurodevelopmental Outcomes After Group B Streptococcus Invasive Disease: A Matched-Cohort Study. (3rd November 2021) - John, Hima B; Arumugam, Asha; Priya, Mohana; Murugesan, Nandhini; Rajendraprasad, Nandhini; Rebekah, Grace; Paul, Proma; Chandna, Jaya; Lawn, Joy E; Santhanam, Sridhar
Abstract: Background: This study is part of a multicountry matched-cohort study designed to estimate the risk of long-term neurodevelopmental impairment (NDI) of children exposed to invasive group B Streptococcus (iGBS). The specific objective of this paper is to compare NDI across domains of iGBS survivors with a matched non iGBS group in our population. Methods: Survivors of iGBS in a South Indian hospital were identified and recruited between January 2020 and April 2021. Cases were compared with age- and gender-matched non iGBS children. Participants were assessed using Bayley Scales of Infant and Toddler Development–3rd edition (BSID-III), Wechsler Preschool and Primary Scale of Intelligence–4th edition (WPPSI-IV), Wechsler Intelligence Scale for Children–5th edition (WISC-V), Child Behavior Checklist (CBCL), and Bruininks-Oseretsky Test of Motor Proficiency, 2nd edition (BOT-2), depending on age. Results: Our cohort comprised 35 GBS-exposed and 65 matched non iGBS children, aged 1–14 years. The iGBS-exposed group had 17 (48.6%) children with impairment in ≥1 domain compared to 25 (38%) in the non iGBS group (unadjusted OR, 1.51; 95% CI, .65–3.46), 9 (26%) children with "multi-domain impairment" compared to 10 (15.4%) in the non iGBS group (unadjusted OR, 1.90; 95% CI, .69–5.24), and 1 (2.9%) child with moderate to severe impairment compared to 3 (4.6%) in the non iGBS group (unadjusted OR, .60; 95% CI, .06–6.07). In the iGBS group, more children had motor impairments compared with the non iGBS group (unadjusted OR, 10.7; 95% CI, 1.19–95.69; P = .034). Conclusions: Children with iGBS seem at higher risk of developing motor impairments compared with a non iGBS group.